Sufism and politics in Morocco - Bouasria, Abdelilah. (London ; New York)
xiii, 232 sayfa
Keywords: “Presenting a political history and sociology of Moroccan Sufism from colonialism to the modern day, this book studies the Sufi model of Master and Disciple in relation to social and political life, comparing the different eras of acquiescent versus dissident Sufism. This comparative fieldwork study offers new perspectives on the connection between the monarchy and mystic realms with a specific coverage of the Boutchichi order and Abdessalam Yassine's Al Adl Wal Ihsane, examining the myth of apolitical Sufism throughout the Middle East and North Africa. Drawing on Michel Foucault and James Scott, this book fuses thinking about the political dimension of Sufism, a “hidden transcript,“ involving power struggles, patronage and justice and its esoteric spiritual ethics of care. Addressing the lacuna in English language literature on the Boutchichi Sufi order in Morocco, this book will be of interest to students and scholars of Islamic Studies, Comparative Politics and the MENA region.“ --